Amygdala Circuitry During Neurofeedback Training and Symptoms’ Change in Adolescents With Varying Depression - Quevedo, Karina; Yuan Teoh, Jia; Engstrom, Maggie; Wedan, Riley; Santana-Gonzalez, Carmen; Zewde, Betanya; Porter, David; Cohen Kadosh, Kathrin (Frontiers in Behavioral Neuroscience, 2020)
Abstract: Typical adolescents have increased limbic engagement unchecked by regulatory medial prefrontal cortex activity as well as heightened self-focus. The resulting emotion dysregulation and self-focused rumination makes adolescents more susceptible to depression and suicide attempts. Heightened self-focus converges with mental illness among depressed adolescents, who deploy exaggerated attention to negative self-relevant stimuli and neglect positive ones as part of depression’s phenomenology. This results in rigid negative self-representations during an identity formative period with potential life-time repercussions. Current empirically supported treatments fail to allay recurrent depression and ensuing suicide risks as well as negative self-representations, which are known to be a risk factor of chronic depression. This study departs from the premise that increasing positive self-processing might be protective against chronic depression particularly during adolescence. The present research is a novel investigation of neurofeedback as a potential treatment alternative for adolescent depression. To enhance positive self-processing, we used the happy self-face as a cue to initiate neurofeedback from the bilateral amygdala and hippocampus and adolescents attempted to upregulate that limbic activity through recall of positive autobiographical memories. We identified limbic functional circuitry engaged during neurofeedback and links to short-term symptoms’ change in depression and rumination. We found that depressed youth showed greater right amygdala to right frontocortical connectivity and lower left amygdala to right frontocortical connectivity compared to healthy controls during neurofeedback vs. control conditions. Depressed youth also showed significant symptom reduction. Connectivity between right amygdala and frontocortical regions were positively correlated with rumination and depression change, but connectivity between frontocortical regions and the left amygdala were negatively correlated with depression change. The results suggest that depressed youth might engage implicit emotion regulation circuitry while healthy youth recruit explicit emotion regulation circuits during neurofeedback. Our findings support a compensatory approach (i.e. target the right amygdala) during future neurofeedback interventions in depressed youth. Future work ought to include a placebo condition or group.